Temporal and Spectral Studies by XMM‐Newton of Jupiter's X‐ray Auroras During a Compression Event. Issue 5 (29th April 2020) - Wibisono, A. D.; Branduardi‐Raymont, G.; Dunn, W. R.; Coates, A. J.; Weigt, D. M.; Jackman, C. M.; Yao, Z. H.; Tao, C.; Allegrini, F.; Grodent, D.; Chatterton, J.; Gerasimova, A.; et al.
Abstract: We report the temporal and spectral results of the first XMM‐Newton observation of Jupiter's X‐ray auroras during a clear magnetospheric compression event on June 2017 as confirmed by data from the Jovian Auroral Distributions Experiment (JADE) instrument onboard Juno. The northern and southern auroras were visible twice and thrice respectively as they rotated in and out of view during the ∼23‐hr (almost 2.5 Jupiter rotations) long XMM‐Newton Jovian‐observing campaign. Previous auroral observations by Chandra and XMM‐Newton have shown that the X‐ray auroras sometimes pulse with a regular period. We applied wavelet and fast Fourier transforms (FFTs) on the auroral light curves to show that, following the compression event, the X‐ray auroras exhibited a recurring 23‐ to 27‐min periodicity that lasted over 12.5 hr (longer than a Jupiter rotation). This periodicity was observed from both the northern and southern auroras, suggesting that the emission from both poles was caused by a shared driver. The soft X‐ray component of the auroras is due to charge exchange processes between precipitating ions and neutrals in Jupiter's atmosphere. We utilized the Atomic Charge Exchange (ACX) spectral package to produce solar wind and iogenic plasma models to fit the auroral spectra in order to identify the origins of these ions. For this observation, the iogenic model gave the best fit, which suggests that the precipitating ions are from iogenic plasma in Jupiter's magnetosphere. Plain Language Summary: The solar wind is a continuous stream of charged particles released by the Sun that flows out toward the edge of the Solar System. It meets obstacles along the way, such as the magnetic fields of planets like the Earth to create a magnetic bubble around them called a magnetosphere. The magnetosphere prevents most of these charged particles from reaching the Earth's atmosphere. Those that make their way through interact with the gas molecules in the atmosphere above the polar regions and cause them to glow to produce the auroras or the northern and southern lights. Jupiter's auroras are much more powerful than the Earth's, and they emit different types of radiation, including X‐rays. It is currently unclear as to what causes Jupiter's X‐ray auroras. Its moon, Io, spews volcanic material into the magnetosphere that can be accelerated into the planet's atmosphere. We created models that consisted of the particles found in the solar wind and in the material from Io's volcanoes to see which one was responsible for Jupiter's X‐ray auroras. In this case, it was Io's volcanoes. We also found that the auroras pulsate every ∼23–27 min in the north and ∼23–33 min in the south. Key Points: XMM‐Newton observed Jupiter on 19 June 2017 during a magnetospheric compression event Fast Fourier transform analysis shows that the X‐ray auroras pulsated over multiple Jupiter rotations Spectral analysis shows precipitating ions from Io and not the solar wind are responsible for the X‐ray auroras